Cloning and characterization of a gene involved in aerial mycelium formation in Streptomyces griseus. - Kudo, N (1995)
A-factor (2-isocapryloyl-3R-hydroxymethyl-gamma-butyrolactone) is essentially required for aerial mycelium formation and streptomycin production in Streptomyces griseus. A DNA fragment which induced aerial mycelium formation and sporulation in an A-factor-deficient mutant strain, S. griseus HH1, was cloned from this strain on a high-copy-number plasmid. Subcloning and nucleotide sequencing revealed that one open reading frame with 218 amino acids, named AmfC, served as a multicopy suppressor of the aerial mycelium-defective phenotype of the A-factor-deficient strain. The amfC gene did not restore A-factor or streptomycin production, indicating that amfC is involved in aerial mycelium formation independently of secondary metabolic function. Disruption of the chromosomal amfC gene in the wild-type S. griseus strain caused a severe reduction in the abundance of spores but no effect on the shape or size of the spores. The infrequent sporulation of the amfC disruptant was reversed by introduction of amfC on a plasmid. The amfC-defective phenotype was also restored by the orf1590 gene but not by the amfR-amfA-amfB gene cluster. Nucleotide sequences homologous to the amfC gene were distributed in all of 12 Streptomyces species tested, including Streptomyces coelicolor A3(2). The amfC homolog of S. coelicolor A3(2) was cloned and its nucleotide sequence was determined. The AmfC products of S. griseus and S. coelicolor A3(2) showed a 60% identity in their amino acid sequences. Introduction of the amfC gene of S. coelicolor A3(2) into strain HH1 induced aerial mycelium formation and sporulation, which suggests that both play the same functional role in morphogenesis in the strains.